Does drinking lead to sex? Daily alcohol-sex behaviors and expectancies among college students - Patrick, Megan E; Maggs, Jennifer L (Psychology of addictive behaviors, 2009)
A within-person multilevel approach was used to model the links between alcohol use and sexual behavior among first-year college students, using up to 14 days of data for each person with occasions (Level 1, N = 2879 days) nested within people (Level 2, N = 218 people; 51.4% male). Between-persons (Level 2) effects were gender, relationship status, person means of alcohol use, and alcohol-sex expectancies for sexual affect and sexual drive. Within-person (Level 1) effects were weekend days, number of drinks consumed, and the interaction between drinks consumed and alcohol-sex expectancies. Independent of average alcohol use, consuming more drinks on a given day was associated with a greater likelihood of oral sex and with experiencing more positive consequences of sex that day. Significant Alcohol Use x Alcohol-Sex Expectancies interactions were found for oral sex and total sex behaviors, indicating that individuals with more positive expectancies were more likely to have sex after drinking. The negative association between drinks and condom use was at a trend level of significance. Results support the potential for promoting sexual health by focusing on cross-behavior expectancies among late adolescents.